Cómic matemático educativo sobre los mayores exponentes del cálculo integral - Amaguaya Uvidia, Genesis Nayely (2025)
The teaching of integral calculus presents significant challenges due to its theoretical complexity, which affects its motivation and comprehension. This study sought to link the stories of renowned mathematicians through short dialogues described through a comic book, centered on the idea of “reading to learn more”. The research follows a quantitative approach with a non-experimental design with a descriptive-propositive, documentary scope, for data collection a 10-question test validated by experts was administered to 13 fifth semester students of the Pedagogy of Experimental Sciences, Mathematics and Physics of the 2024-2S academic period. The results revealed that it is important to reconfigure the teaching strategies to address the problems present in the conceptual and procedural contents. 84.7% indicated that it is necessary to use didactic resources, that classes should be personalized and that the exercises proposed in the classroom should be articulated to daily life. In addition, 92.4% considered that visual resources are a good strategy for learning integral calculus. Therefore, the research identified the potential of the management of a comic book with short stories of outstanding mathematicians, supported by the fact that 76.9% of the students stated that they find it attractive to learn in this way and 92.4% thought that it would help them learn better than reading a printed page. In conclusion, the combination of visual and narrative elements facilitates the assimilation of complex concepts and contributes to more meaningful learning. It is recommended to expand the use of innovative didactic materials in the teaching of mathematics to enhance students' interest.